Between likes and lows: Exploring how social networking, privacy, and loneliness shape college students’ satisfaction - Tarik N. MOHAMED; Rania A. MOURAD; Muhammad AZZEDIN (Journal of Health and Social Sciences)
Introduction: The rise of online social networking has transformed how individuals interact, raising concerns about its impact on privacy, loneliness, and life satisfaction. This study explores the direct and indirect relationships among these variables, with a focus on institutional (vertical) and peer (horizontal) privacy concerns, social and emotional loneliness, and overall satisfaction among college students. Methods: This study analyzed A sample of 778 college students 39.7% are females participated in this study. A conceptual model was tested to examine the effects of social networking use on privacy concerns, loneliness, and life satisfaction. Structural equation modeling was used to analyze the relationships among these variables. Results: Findings revealed that increased social networking use was positively associated with privacy concerns at the institutional level (β = −.242, p < .01) and peer level (β = −.205, p < .001). Institutional privacy concerns uniquely mediated life satisfaction, highlighting their relevance in structured settings like universities. Furthermore, social networking use predicted higher emotional loneliness and lower life satisfaction, indicating that online interactions may fail to address deeper emotional needs. However, no significant relationship emerged between social networking use and social loneliness, suggesting that broader social needs may depend on offline interactions. Discussion: These results demonstrate the role of social networking in shaping college students’ well-being. While online platforms offer connections, they may also heighten privacy concerns and emotional loneliness, impacting life satisfaction. Institutional privacy concerns play a critical mediating role, highlighting the importance of privacy in academic settings.